2020
DOI: 10.1177/0190272520961408
|View full text |Cite
|
Sign up to set email alerts
|

Do White People See Variation in Black Skin Tones? Reexamining a Purported Outgroup Homogeneity Effect

Abstract: Previous research has reported that white survey interviewers remember black respondents’ skin tones in a much narrower range than recollections by black interviewers. This finding has been used to suggest that, in line with the one-drop rule, whites do not perceive meaningful differences between light- and dark-skinned black people. The authors reanalyze evidence thought to demonstrate relative homogeneity in white interviewers’ evaluation of black skin tones. In contrast to previous studies, this examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…At the same time, it is important to note that how phenotypically prototypical an individual is perceived can also depend on the perceiver. For instance, White Americans under negative circumstances involving rejection or economic scarcity show a tendency to perceive Black Americans as more phenotypically prototypical (Krosch & Amodio, 2014;Sacco et al, 2011) (but see Hannon et al, 2020). Thus, both higherorder and cue-level influences likely have main and interactive effects.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it is important to note that how phenotypically prototypical an individual is perceived can also depend on the perceiver. For instance, White Americans under negative circumstances involving rejection or economic scarcity show a tendency to perceive Black Americans as more phenotypically prototypical (Krosch & Amodio, 2014;Sacco et al, 2011) (but see Hannon et al, 2020). Thus, both higherorder and cue-level influences likely have main and interactive effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, White perceivers have also been found to observe less variation in skin color overall when the targets are Black, rating Black survey respondents as more homogeneous and darker on average than Black perceivers who rated the same subjects (Hill 2002). Although recent research has questioned the robustness of this finding in survey settings (Hannon et al 2021), it aligns with decades of lab-based studies on the ''outgroup homogeneity'' effect wherein individuals have been found to perceive more physical variation among ingroup than outgroup members (Linville et al 1989;Quattrone and Jones 1980). Following this line of research, we add an additional modification to our initial hypothesis: that interracial discrimination by skin color in the housing market may be less prevalent than intraracial discrimination (Hypothesis 4).…”
Section: Variation In Colorism Within and Between Racial Groupsmentioning
confidence: 99%
“…Others argue that the observer's own race and contact with members of a given race group affect their perceptions, particularly when measuring the accuracy of an observer choosing a target from an eyewitness lineup (Hannon and DeFina 2014;Sporer 2001). Still others suggest that experiencing racial discrimination changes a perceiver's accuracy (Blascovich et al 1997), that skin-tone bias affects perception (Hill 2002;Maddox and Gray 2002), or that whites do not perceive skin tone differences in African-Americans (Hannon et al 2020). Here, I examine the theories associated with these claims, starting with aspects of the observer, moving to aspects of the target, and then looking at both simultaneously.…”
Section: Perceptions Of Racementioning
confidence: 99%